Identification and Quantification of Defects in the Cation Ordering in Mg/Al Layered Double Hydroxides - Cadars, S; Layrac, G; Gerardin, C; Deschamps, M; Yates, JR; Tichit, D; Massiot, D (2011)
Cation ordering is believed to have crucial effects on many of the physicochemical properties that make layered double hydroxides (LDHs) materials of considerable interest as host structures for drug delivery systems, nanocomposite materials, or for catalysis. Here we first unambiguously confirm that solid-state 1H NMR at fast (60-65 kHz) magic-angle spinning (MAS) can be used to distinguish and quantify the different local Mg nAl 3-nOH (n = 1, 2, and 3) environments of hydroxyl groups in LDH layers. By combining different solid-state 1H and 27Al one- and two-dimensional NMR measurements with first-principles calculations, we demonstrate that, although globally ordered, the cation distribution in Al-rich Mg/Al-2 LDHs contains detectable amounts of Al clustering. Though small, the fraction of Al atoms misplaced with respect to the perfectly ordered cation arrangement (where Al-Al pairs are avoided) could be quantified. Their number is shown to counterbalance the number of misplaced Mg atoms for a Mg/Al ratio of 2 and to strongly decrease for reduced Al contents. This establishes that, although not favored, Al-O-Al linkages are not excluded in Al-richer LDH materials, a finding that will strongly impact our understanding of the local acidity of these materials and their widely exploited anion exchange and reconstruction properties. © 2011 American Chemical Society.